Reply to ’Pancreatic Adenocarcinoma with Supraclavicular Lymph Node Metastasis: Is This the Virchow’s Node?’ - Soman, Arundhati D; Borad, Mitesh J (JOP. Journal of the Pancreas, 2011)
No abstract available. Image: Mayo Clinic Arizona. Scottsdale, AZ, USA